A mouse monoclonal antibody against dengue virus type 1 mochizuki strain targeting envelope protein domain II and displaying strongly neutralizing but not enhancing activity - Atsushi Yamanaka (2018)
Dengue fever and its more severe form, dengue hemorrhagic fever, are major global concerns. Infection-enhancing antibodies are major factors hypothetically contributing to increased disease severity. In this study, we generated 26 monoclonal antibodies (MAbs) against the dengue virus type 1 Mochizuki strain. We selected this strain because a relatively large number of unique and rare amino acids were found on its envelope protein. Although most MAbs showing neutralizing activities exhibited enhancing activities at subneutralizing doses, one MAb (D1-IV-7F4 [7F4]) displayed neutralizing activities without showing enhancing activities at lower concentrations. In contrast, another MAb (D1-V-3H12 [3H12]) exhibited only enhancing activities, which were suppressed by pretreatment of cells with anti-FcγRIIa. Although antibody engineering revealed that antibody subclass significantly affected 7F4 (IgG3) and 3H12 (IgG1) activities, neutralizing/enhancing activities were also dependent on the epitope targeted by the antibody. 7F4 recognized an epitope on the envelope protein containing E118 (domain II) and had a neutralizing activity 10- to 1,000-fold stronger than the neutralizing activity of previously reported human or humanized neutralizing MAbs targeting domain I and/or domain II. An epitope-blocking enzyme-linked immunosorbent assay (ELISA) indicated that a dengue virus-immune population possessed antibodies sharing an epitope with 7F4. Our results demonstrating induction of these antibody species (7F4 and 3H12) in Mochizuki-immunized mice may have implications for dengue vaccine strategies designed to minimize induction of enhancing antibodies in vaccinated humans. © 2013, American Society for Microbiology.